Comparison of Injection Characteristics and Droplet Distribution on Crude Palm Oil and Diesel Using CFD - Suprianto, Teguh; Darmansyah, Darmansyah; Hasbi, Muhammad (Eksergi, 2022)
CPO (Crude Palm Oil) is a potential renewablefuel as a substitute for fossil fuels used in internal combustionengines. An important parameter that affects the combustion ofan engine with an injection system is the characteristics of thefuel spray. This research was conducted using ComputationalFluid Dynamics (CFD) software to model the atomizationprocess that occurs when CPO and diesel fuel are injected witha pressurized atomizer. The modeling shows the characteristicsof the spray which include the shape of the spray and the dropletdiameter distribution. These characteristics are presented withspray images, droplet diameter distribution graphs, and velocitydistribution graphs. Simulations show that at temperaturesabove 75 °C and 100 °C, CPO spray produces droplet shapes anddistributions that are almost the same as diesel spray. On theother hand, diesel injection spray produces a lower droplet size.The highest droplet size distribution is at 12-16 microns.